Pengaruh Literasi Digital terhadap Minat Berwirausaha Mahasiswa Prodi Manajemen Universitas Negeri Medan - Olivia Sembiring Sembiring; Okta Viani Kristin Kristin; Nabila Boru Lubis; Anggita Kinanti; Desmila Atheja Syahfitri Lingga; Saidun Hutasuhut (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Digital transformation has reshaped entrepreneurial practices, requiring students to master digital competencies in order to identify opportunities and build innovative ventures. This study aims to examine the influence of digital literacy on students’ entrepreneurial interest within the Management Study Program at Universitas Negeri Medan. Using a quantitative survey approach, data were collected from 100 students selected through simple random sampling. The questionnaire employed validated indicators of digital literacy and entrepreneurial interest, and the data were analyzed through normality testing, linearity testing, and simple linear regression using SPSS 26. The findings indicate that digital literacy has a positive and significant effect on entrepreneurial interest, as shown by a regression coefficient of 0.405 and a significance value of 0.000. The standardized beta coefficient of 0.444 demonstrates a moderately strong contribution of digital literacy in shaping entrepreneurial interest, suggesting that students with stronger digital capabilities tend to be more confident and motivated to pursue entrepreneurial activities. These results highlight the importance of strengthening digital competencies in higher education to prepare students for opportunities in the digital economy.